Salivary IL-17A, IL-17F, and TNF-α Are Associated with Disease Advancement in Patients with Oral and Oropharyngeal Cancer - Kinga Zielińska; Bożenna Karczmarek-Borowska; Konrad Kwaśniak; Justyna Czarnik-Kwaśniak; Aleksandra Ludwin; Bogumił Lewandowski; Jacek Tabarkiewicz (Journal of Immunology Research)
Delayed diagnosis of oral cavity and oropharyngeal cancer is associated with a poor prognosis. Despite progress in systemic therapy and radiotherapy, there has only been a slight improvement in the five-year survival rate. A non-invasive diagnostic method that consists of an assessment of specific proteins in saliva samples may significantly facilitate assessment of treatment results in patients diagnosed with oral and oropharyngeal cancer. The aim of this study was to assess the levels of IL-17 and TNF-α in the saliva of patients with oral and oropharyngeal cancer. The study was conducted prior to treatment in patients hospitalized in the Frederic Chopin Provincial Specialist Hospital No. 1 in Rzeszów, Poland. Saliva samples were collected from subjects on an empty stomach. Cytokine concentrations in the saliva were measured with ELISA and Luminex Multiplex Assays. The higher salivary concentrations of IL-17A, IL-17F, and TNF-α were significantly associated with disease advancement. Lower levels of IL-17A were associated with colonization of the oral cavity with aerobic bacteria. On the other hand, higher concentration of TNF-α was observed in patients with positive aerobic culture of oral swabs. Our results suggest that IL-17A, IL-17F, and TNF-α measured in the saliva may be a potential biomarker for cancer of the oral cavity and oropharynx.